Senat i senatorowie za panowania Flawiuszy (Tabularium Historiae, 2019)
The Flavians’ rule brought numerous changes of the composition and the importance of the senatorial order. By completing its composition the Flavians gained a circle of loyal supporters. The Senate, however, did not lose its significance although Vespasian successfully camouflaged the fact that the real decisions were made somewhere else. The situation changed completely during Domitian’s rule, Executions of members of the senatorial elite (even if relatively not very common) did not enhance the freedom of speech. They were rightly treated as an element of intimidation and terror. Vespasian could regularily influence the shape of the elites of power as he decided who was supposed to receive the office of consul. One of characteristic features of his reign was the fact that he kept the office to himself and his sons. It meant that, in practice, the access to the office of consul ordinarius, the most desired and prestigious office in the state, was seriously limited. In order not to decrease the numer of ex consuls who were indispensable to perform the most crucial functions in the state the Flavians increased the numer of supplementary consuls who were appointed annually. The situation partly changed under Domitian as after the year 88 the Caesar held the office only three times. Domitian was quite generous in promoting members of patrician families to the office of consul. At the same time he made effort to reward people who had been layal and worthy to the Caesarian family during the civil war and who were later on, for different reasons,debarred from posts of authority. Governorship of strategic provinces, which required great skill and also the caesar’s trust, was most commonly granted to the closest members of the family. The proconsulships of Asia and Africa were dominated by the most distinguished and honoured Italians. During the reigns of Vespasian and Titus only few proconsuls were promoted to the office of consul. The situation changed under Domitian’s rule. According to the available data as many as 12 out of 25 well known proconsuls became consuls. The caesar was also more willing to help the so called second rank senators fulfill their ambitions. They normally did not have much chance to make a great political career. Holding one of the three tutelages in the area of Rome was for some senators the pinnacle of their careers. There were a few senators who held the office but not much is known about them. The prefecture of Rome was another of the most desirable posts in the state. John of Lydia, a Byzantine writer, claims that Domitian played an important role in reforming the office. However, none of the sources on the subject confirms his claim. This is probably one of many false pieces of information provided by the writer.